Denture Induced Stomatitis-A Case Report - Ahsan Inayat; Syed Zahid Hassan; Ayesha Aziz; Rida Ibrahim (International Journal of Endorsing Health Science Research, 2019)
Background: Denture hygiene habits are liable to change from one person to another. There has been a close relationship between irregular denture surfaces, poor oral hygiene or ill-fitted denture and opportunistic oral microorganism which leads to diseases like denture induced stomatitis.